ANALISA LAPORAN KEUANGAN PADA PT HOLCIM INDONESIA Tbk - Hijroini Fajaryati (Politeknik Raflesia Press, 2020)
The purpose of this study is to determine the company's financial performance and ability To pay short-term obligations and obligations of PT Holcim Indonesia Tbk for the 2017-2018 period. This research includes quantitative and descriptive research, namely research that uses a calculation process and decomposes sentences in order to provide a clear picture of the problem under study. The results of research at PT Holcim Indonesia Tbk can be concluded that the liquidity ratio which includes the current ratio and the quick ratio for the 2017-2018 period can be concluded that the company has a poor level of liquidity because the yield value of liquidity is <1%. For the solvency ratio for the 2017-2018 period, which includes a debt to asset ratio owned by the company of 0.6%, it can be stated that it is not good because it exceeds 0.5% of the set standard and the company's debt to equity ratio of 1.9% can be stated to be not good. because more than 1% of the standards are set and it can be concluded from the results of research on solvency ratios, it can be concluded that the company's ability to pay its obligations is still far from being expected to finance debt that is in the company and it can be said that it is not good.